Peran Masyarakat Dalam Pembangunan Desa Di Desa Purba Dolok Kecamatan Doloksanggul Kabupaten Humbang Hasundutan - Purba, Januarny; Nasution, Irwan; Kurniaty, Evi Yunita (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
The role of the community in development is still relatively passive, this can be seen from some people who do not care about the village development that will be carried out. The purpose of this study is to find out the role of the community in development and to find out the obstacles to the role of the community in village development in the village of Purba Dolok. In this study, the type of research carried out by the author is a qualitative descriptive approach method, which explains the problems that exist in the form of words and writing in every existing event. Indicators of the role of the Purba Dolok village community as a policy role, in the form of arguments such as building placement, paying attention to building durability and building maintenance. Then, the role as a strategy where the community cooperates with village officials in developing strategies for the implementation of development in the form of site preparation, adjustment of budget funds and the formation of working groups. The role as communication, in this case, the communication of the village community and village officials provide information to the community through the head of the hamlet who is responsible for the environment of each hamlet. The role as a dispute resolution tool, in this case the way that is carried out in reducing differences of opinion and conflicts that arise, the holding of village deliberations for voting in order to overcome differences of opinion that arise when village deliberations are held.